MENJAGA HARMONI: MEMADUKAN BUDAYA MINAHASA (RITUAL KAMPETAN) DAN PRINSIP KEKRISTENAN DALAM KEHIDUPAN BER-JEMAAT - Kaensige, Mariska Theodora (PT. Giat Konseling Nusantara, 2025)
This article explores the importance of religious moderation in harmonizing local culture, particularly the Kampetan ritual in Minahasa, with Christian principles. As a cultural heritage, the Kampetan ritual reflects values such as community solidarity, respect for ancestors, and togetherness. However, certain elements of the ritual, such as ancestor invocation, conflict with biblical teachings. Through religious moderation, positive cultural elements can be preserved and imbued with new meanings aligned with the Word of God. This approach includes transforming cultural symbols, such as the